Contextos geográficos da AIDS e os espaços vividos por jovens com HIV em Presidente Prudente - SP - Pedroso, Mateus Fachin [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
There are currently more than 34, 9 million people living with HIV / AIDS in the world. Today it is one of the diseases that has affected the world population the most, as it manifests itself as a problem that transcends all scales, reaching different segments, from the local to the global. It is in this context that the present monograph entitled Geographic contexts of AIDS and the spaces lived by young people with HIV in Presidente Prudente - SP aims to understand the situations of vulnerability to HIV infection in the young layer of Presidente Prudente - SP through immersion In the geographic context of the subjects, making understand the collective health from the Geography. This study was built under the aegis of Qualitative Research, through the analysis of the speeches reports obtained through interviews, since this approach allows a deep and complex reflection, which makes possible the approximation of the geographical contexts of young people living with HIV / AIDS, Issues that affect the subjects' health and health services. There were innumerable challenges encountered in the accomplishment of the work, which demonstrated to us in fact the reality lived by these subjects. From the analysis carried out, we visualize in the research results, how the young prudentinos understand the geographic space, and how it is constructed, appropriate and lived. Such considerations allow us to understand the urban space under a different perspective, providing other new discussions that bring the experiences, their practices and actions in a reflexive sense in the geographical field, in relation to HIV / AIDS, to the youth and their bodies. And, it is from this geographical view that we prioritize the understanding of the subjects and their contexts, in which the speeches that characterize and evidence the socio-spatial markings of HIV / AIDS are expressed

Atualmente são mais de 34, 9 milhões de pessoas vivendo com o HIV/AIDS no mundo. Hoje é uma das doenças que mais tem afetado a população mundial, pois, manifesta-se como uma problemática que transpassa todas as escalas, atingindo diversos segmentos, desde o local ao global. É neste âmago que a presente monografia intitulada Contextos geográficos da AIDS e os espaços vividos por jovens com HIV em Presidente Prudente - SP tem como objetivo compreender as situações de vulnerabilidades à infecção pelo HIV na camada jovem de Presidente Prudente - SP através da imersão no contexto geográfico dos sujeitos, fazendo-se compreender a saúde coletiva a partir da Geografia. Este estudo foi construído sob a égide da Pesquisa Qualitativa, através das análises dos discursos obtidos por meio de entrevistas, já que esta abordagem permite uma reflexão profunda e complexa, que viabiliza a aproximação dos contextos geográficos dos jovens vivendo com HIV/AIDS evidenciando as problemáticas que tangem a saúde dos sujeitos e aos serviços de saúde. Foram inúmeros os desafios encontrados na realização do trabalho, que nos demonstraram de fato a realidade vivida por estes sujeitos. A partir das análises realizadas, visualizamos nos resultados de pesquisa, como os jovens prudentinos compreendem o espaço geográfico, e de como este é construído, apropriado e vivido. Tais considerações nos possibilitam a compreensão do espaço urbano sob um olhar diferenciado, proporcionando outras novas discussões que agregam em sentido reflexivo no campo geográfico, em relação ao HIV/AIDS, aos jovens e seus corpos, as experiências, suas práticas e ações. E, é a partir deste olhar geográfico, que priorizamos o entendimento dos sujeitos e seus contextos, nos quais são expressas as falas que caracterizam e evidenciam as marcas socioespaciais advindas do HIV/AIDS
Keywords: Geografia; AIDS (Doença) - Presidente Prudente (SP); HIV (Vírus) - Presidente Prudente (SP); Geografia humana; Geography